PO218 Neuroaccess: breaking the cycle: zambia 2016. (1st December 2017) - Bonello, Michael; Williamson, John C; Nightingale, Sam; Phukan, Julie; Siddiqi, Omar K; Solomon, Tom; Michael, Benedict D
Abstract : Neurological disease is responsible for a huge burden of death and disability in sub-Saharan Africa. However, average number of Neurologists in these countries can be as low as 0.3/million. Consequently, most doctors will qualify from medical school without having been taught by a Neurologist. NeuroAccess aims to provide a sustainable programme of targeted clinical neurology education in Zambia and Mozambique. The NeuroAccess team is a small group of Registrars, Clinical Lecturers, and Consultants, who provide a bi-annual intensive clinical teaching programme to doctors and students, in coordination with the local curriculum. With the support of the ABN, the Encephalitis society and the UK-based NeuroPACES course, NeuroAccess is delivered annually since 2013 providing teaching to an estimate of 60 medical students and 20 doctors on each visit. The whole programme is made possible thanks to colleagues working on the ground throughout the year. In collaboration with these locally based, physicians the aim is to incorporate NeuroAccess in a long-term programme of formal post-graduate neurological specialist training. Our aim is to improve the depth and breadth of practical skills in clinical neurology to empower a cadre of local doctors to manage the many neurological problems in these countries.